High Incidence of Escherichia coli – Urinary Tract Infection in Pregnant Women in Iraq - Hanaa Jabbar Rasheed; Khairi Jameel Al-Ruaby; Alwan Abed Hamadi AlQshawi (World Journal of Experimental Biosciences, 2022)
Escherichia coli is considered as one of the most important microbial causes of urinary tract infections (UTIs) in women. The UTI caused by E. coli increased in the last years and the resistance strains to wide spectrum also increased with time. The present study aims to evaluate the incidence of E. coli that is responsible for UTI in women and evaluate the difference between pregnant and non-pregnant women in Iraq. The urine samples were collected from 170 women who visited the public hospital in Waist City. The clinical cases were divided into symptomatic cases and asymptomatic cases. E. coli was identified by using the biochemical test, API20E system, and Vitek II System. The Bergy’s Manual of Systematic Bacteriology was followed to identify the species of E. coli. The current study showed that the highest percentage of UTI infection with E. coli was seen in symptomatic women aged 25-29 years old, and the highest percentage of asymptomatic UTI infection in women aged range 25-29 years. The highest percentage of UTI infection with E. coli was seen in pregnant women as compared with non-pregnant women (P
Keywords: API20E system, Escherichia coli, Biochemical test, Vitek II System, Urinary tract infection.